Hackberry emperor, Asterocampa celtis (Boisduval & Leconte) (Insecta: Lepidoptera: Nymphalidae: Apaturinae) - Donald W. Hall; Jerry F. Butler (EDIS)
EENY-453, a 5-page illustrated fact sheet by Donald W. Hall and Jerry F. Butler, is part of the Featured Creatures collection. It describes this common butterfly of river bottoms, its distribution, description, life cycle and biology, hosts, and economic importance. Includes references. Published by the UF Department of Entomology and Nematology, June 2009.